Religion matters: what sociology teaches us about religion in our world - Emerson, Michael O. (Prentice Hall, 2011)
News flashes -- Getting acquainted -- Why religion? -- You believe what? -- Downloading God, big box churches -- And the crystal shop around the corner -- The shape of religion -- Why can't we all just get along? -- God's not dead (and neither is the Goddess!) -- Our God rules (yours doesn't) -- Religion, conflict, and the state -- Divine rights and casting down the mighty from their thrones -- Give us our due -- Religion, identity, and social inequalities -- Adam, Eve, and Steve -- The (not-so-great) color wall of the U.S. -- Who brought the enchiladas to my Bar Mitzvah? -- More big questions -- Godless science, irrational religion -- The end of days religion and environmentalism -- Do we need God to do good?